2003
DOI: 10.1002/ajmg.b.20012
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism Screening of PIP5K2A: A Candidate Gene for Chromosome 10p‐Linked Psychiatric Disorders

Abstract: Lithium is a potent noncompetitive inhibitor of inositol monophosphatases, enzymes involved in phosphoinositide (PI) and inositol phosphate metabolism. A critical component of the PI pathway is phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P(2)), which is hydrolyzed to second messengers and has a direct role in synaptic vesicle function. Interestingly, a number of genes involved in the synthesis and dephosphorylation of PtdIns(4,5)P(2) are found in regions of the genome previously mapped in bipolar disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…It has the highest catalytic activity among the three isoforms. PIP4K2A is responsible for the clearance of PI(5)P upon oxidative stress (16) and its mutations are associated with leukemia (17)(18)(19) and schizophrenia (20)(21)(22).…”
Section: Pip4k2a Is Required For Intracellular Cholesterol Transportmentioning
confidence: 99%
“…It has the highest catalytic activity among the three isoforms. PIP4K2A is responsible for the clearance of PI(5)P upon oxidative stress (16) and its mutations are associated with leukemia (17)(18)(19) and schizophrenia (20)(21)(22).…”
Section: Pip4k2a Is Required For Intracellular Cholesterol Transportmentioning
confidence: 99%
“…In addition to the Dutch study mentioned above, 65 this polymorphism was tested in another case-control sample comprising 176 patients with schizophrenia and 178 controls from North America with European background and from Israel, as well as in a sample comprising 198 bipolar patients and 212 controls from USA and the Czech Republic, 77 following up our preliminary report on association of the N251S polymorphism in schizophrenia at the IXth World Congress for Psychiatric Genetics 2001. 64 Association was not detected with this particular variant, but a modest difference was found in the distribution of alleles from the CT repeat pik53 þ 54 (M45), which was also associated in our sample (Table 1, P = 0.026).…”
Section: -36mentioning
confidence: 99%
“…Its product is involved in the phosphoinositide signal transduction system, and it is also harbored by 10p12, a chromosomal region showing linkage to schizophrenia and bipolar disorder, although less consistently than other linkage regions [Stopkova et al, 2003]. Two association studies have reported several SNPs in PIP5K2A to be associated with schizophrenia [Stopkova et al, 2005;Schwab et al, 2006].…”
Section: Introductionmentioning
confidence: 98%